CORPORATE GOVERNANCE, KOMITE AUDIT, KUALITAS AUDIT, DAN MANAJEMEN PAJAK (Studi Empiris Pada Perusahaan Yang Terdaftar di Indeks LQ45 Periode 2014-2018) - Deo Novrin Hasiholan Damanik; Dul Mu'id (Diponegoro Journal of Accounting, 2019)
The aim of this study is to examine the influence of corporate governance, audit committee and audit quality on tax management of the company. Independent variable used in this study are corporate governance which is measured by proxies of number of commissioners, percentage of independent commissioner, compensation of board of commissioner and board of directors, audit committee is measured by proxies of number of audit committee of the company while audit quality is proxied by size of public accountant firm. Dependent variable is tax management which is measured by effective tax rate (ETR)The population used in this study consist of firms that listed on LQ45 index on Indonesia Stock Exchange in 2014-2018. The sampling method used in this study is purposive sampling and obtained 23 companies every year. This study uses multiple regression analysis for hypotheses testing.The results of this study showed that number of commissioner has no effect on tax management measured by tax expense and by cash tax paid, percentage of independent commissioner has negative effect on tax management measured by tax expense but has no effect on tax management measured by cash paid, compensation of board commissioner and directors has negative effect on tax management measured by tax expense and by cash paid, audit committee has no effect on tax management measured by tax expense but has negative effect on tax management measured by cash paid, audit quality has negative effect on tax management measured by tax expense and has no effect on tax management measured by cash paid.